Microglia in Neurological Diseases: A Road Map to Brain-Disease Dependent-Inflammatory Response - Bachiller, Sara; Jiménez-Ferrer, Itzia; Paulus, Agnes; Yang, Yiyi; Swanberg, Maria; Deierborg, Tomas; Boza-Serrano, Antonio (Frontiers in Cellular Neuroscience, 2018)
Microglia represent a specialized population of macrophages-like cells in the central nervous system (CNS) considered immune sentinels that are capable of orchestrating a potent inflammatory response. Microglia are also involved in synaptic organizatio, trophic neuronal support during development, phagocytosis of apoptotic cells in the developing brain, myelin turnover, control of neuronal excitability, phagocytic debris removal as well as brain protection and repair. Microglial response is pathology dependent and affects to immune, metabolic. In this review, we will shed light on microglial activation depending on the disease context and the influence of factors such as aging, environment or cell-to-cell interaction.